PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBLOG PADA MATERI PROGRAM LINEAR KELAS XI - Andre Andre; Bistari Bistari; Rustam Rustam (UNIVERSITAS TANJUNGPURA, 2022)
This study aims to produce a weblog on linear programming material that is suitable for use in the learning process. This research is a research and development (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The test subjects in this study were 25 students of class XI SMAS Mujahidin Pontianak, while the object of this research was a weblog with linear programming material. The appropriateness of the learning media was assessed by media experts, material experts, and teachers before a limited trial was carried out by students.learning media weblog that has been developed according to material experts is obtained with a percentage of 75% with a decent category, according to media experts it is obtained a percentage of 77.5% with a very decent category, and according to the teacher's assessment a percentage of 82.5% with a very decent category. Meanwhile, for student responses, the percentage is 81.4% with a very decent category. Based learning media weblog on linear programming material is feasible to use in learning.